The complete guide to fencing - Barth, B.; Beck, E.; Janka, C. (Meyer & Meyer Sport (UK) Ltd., 2017)
This teaching and reference book covers the most important concepts of training theory in the sport of fencing and their methodological application. Supplemented by the general teaching methods and experiences of Germany's most successful trainers, findings, theories, and methods of training, science-oriented basic concepts are integrated here with application-oriented editing.